Assessing inequalities in geographical access to emergency medical services in metropolitan Lisbon: a cross-sectional and ecological study - Katielle Susane do Nascimento Silva; Miguel Padeiro (BMJ Open)
Objectives Studies have suggested that material deprivation is strongly associated with negative health outcomes, and lower usage of various levels of healthcare. We aim to analyse geographical access to emergency medical services (EMSs) and hospital emergency units by EMS in relation to deprivation in the Lisbon Metropolitan Area (LMA), Portugal.Design This study estimates road network-based access times from the centroids of statistical sections (census block groups equivalent) to locations of EMS and hospital emergency services. Each statistical section has been linked to a Material Deprivation Index (MDI). A non-parametric analysis of variance (ANOVA) was undertaken to compare MDI-linked statistical sections in terms of access to emergency care. Geographical access analysis was conducted for 2018.Primary outcome measure Road network-based access time (in minutes) for EMSs to statistical sections and then on to emergency units in hospitals.Results Overall, 82.4% of the LMA population is located less than a 10 min drive from an EMS without transport, and 99.1% from an EMS with transport. Travel time from EMS with transport to hospital is potentially less than 20 min for 95.2% of the population. However, 63.1% of residents living beyond a 30 min threshold (total time from emergency call to hospital arrival) are in areas with very high MDI (18.8% in high MDI, 13.3% in medium MDI, 4.7% in low MDI, 0% in very low MDI). Kruskal-Wallis ANOVA confirms discrepancies in access times between better-off and poorer areas.Conclusion Poorer areas experience worse geographical access to EMS and hospital emergency units. More research is needed to explore the quality of services and their outcomes, and to refine the analysis by focusing on specific vulnerable groups.